Sexual Activity among Children under the Age of 15 A Case Report - Karbeyaz, Kenan; Dinç, Ceysu; Balcı, Yasemin (The Bulletin of Legal Medicine, 2016)
Children’s information about legislations related to sexual health and sexual behaviours are inadequate in our country. The aim in this case report was to discuss the legal process about sexual interaction between two children under 15 years old. It is important to provide children with an adequate education about sexual behaviour. It is believed that a detailed legal regulation by also taking experts opinions is needed for the childhood.Keywords: Among Children, Sexuality, Child, Forensic Medicine.
Keywords: among children; sexuality; child; forensic medicine